Plasma endoxifen and 4-hydroxytamoxifen levels in CYP2D6(C100T) carrying breast cancer patients and association with serum cholesterol - Chao, Ta-Chung; Pan, Wen-Chi; Tsai, Yi-Fang; Chou, Yueh-Ching; Liu, Yu-Rong; Wang, Sheng-Fan; Chen, Ying-Jen; Souček, Pavel; Ueng, Yune-Fang (Toxicology and applied pharmacology, 2019)
Breast cancer patients with high cholesterol biosynthesis signature had poorer therapeutic outcome. Cytochrome P450 (CYP) 2D6 is crucial in the oxidation of tamoxifen to generate active metabolites, 4-hydroxytamoxifen and endoxifen. CYP2D6 variants with C100T substitution encode null or poor functional proteins. This study aims to examine the association of C100T genotypes and serum lipid levels with plasma drug levels in patients. Plasma tamoxifen concentration was positively associated with serum triglyceride concentration, adjusting for age and C100T genotype. Overweight (body mass index >24.0) patients with high serum cholesterol (≥200 mg/dL) had increased risks of ineffective endoxifen levels (<5.97 ng/mL). Compared to the low-cholesterol group, the high-cholesterol group had a lower 4-hydroxytamoxifen or endoxifen level in T/T carriers. In T/T carriers, the high-cholesterol group had an increased risk of an ineffective endoxifen level. Metastasis, hot flash/flushing, and high alanine transaminase did not relate to plasma 4-hydroxytamoxifen or endoxifen levels. Results indicate that C100T and high serum cholesterol are risk factors of ineffective endoxifen levels in Taiwanese breast cancer patients. These findings warrant further studies of a large hypercholesterolemic population to examine the outcome of increased doses of tamoxifen.
Keywords: Female; lidé středního věku; Cytochrome P-450 CYP2D6; Breast Neoplasms; tamoxifen; Antineoplastic Agents, Hormonal; nádory prsu; cholesterol; senioři nad 80 let; Humans; dospělí; Cholesterol; Phenotype; Tamoxifen; cytochrom P-450 CYP2D6; lidé; fenotyp; Middle Aged; Aged, 80 and over; senioři; ženské pohlaví; genotyp; Aged; Adult; hormonální protinádorové látky; Genotype